2019
DOI: 10.4081/dr.2019.7675
|View full text |Cite
|
Sign up to set email alerts
|

Clinical picture, diagnosis and treatment of rosacea, complicated by Demodex mites

Abstract: The article analyzes the clinical picture and course of rosacea in patients with Demodex mites. It presents the advantages of using the method of confocal laser scanning microscopy over the method of light microscopy of facial skin scrapes. The aimes were to study the influence of Demodex mites on the clinical picture and course of rosacea; to compare laboratory and instrumental diagnostic methods for detecting Demodex mites; to evaluate the effectiveness of external therapy aimed at eliminating Demodex mites.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 20 publications
0
21
1
3
Order By: Relevance
“…The previous studies have shown the prevalence of ocular demodicosis in blepharitis patients between 67.2% and 83.7% (39-42). Demodex is not just responsible for blepharitis, it has also significant roles in meibomian gland disorder, (45) and rosacea (46). All these diseases are frequently seen in the community and require continuous follow-up for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies have shown the prevalence of ocular demodicosis in blepharitis patients between 67.2% and 83.7% (39-42). Demodex is not just responsible for blepharitis, it has also significant roles in meibomian gland disorder, (45) and rosacea (46). All these diseases are frequently seen in the community and require continuous follow-up for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…30 Demodex are the most successful ectoparasites of the body; they are commonly found in individuals older than 40 years and are virtually universal after age 45 years. 31,32 Each Demodex has 8 short legs, 4 on each side of their upper body, that advance in a peculiar rotary fashion, which limits its locomotion to 8 to 16 mm/h 29,33 (Fig. 1).…”
Section: Classification and Life Cyclementioning
confidence: 99%
“…Mechanism of metronidazole action in rosacea had been suggested as anti-inflammatory effects and anti-parasitic activity on Demodex folliculorum 9 10 11 . Recently, the effect of D. folliculorum in increasing the duration of rosacea and probability of recurrence has been described 12 . There have been few reports of systemic metronidazole therapy for Demodex -associated diseases including rosacea and Demodicidosis 5 6 7 8 13 14 15 , which encouraged us to investigate whether the early combination use of oral metronidazole with minocycline could induce rapid resolution and prevention of relapse of rosacea.…”
Section: Introductionmentioning
confidence: 99%